PENDAMPINGAN PEMBELAJARAN DIMASA PANDEMI COVID-19 DI DESA KENDENAN KABUPATEN ENREKANG - Bahruddin Bahruddin; Muh. Yasin; Amalia Amalia; Fatmala Dewi; Ridwan Ridwan; Nurseftibella Fatwa; Muhammad Hernan Arya; Reski Nadia; Nur Alamsyah; Muh. Yahimnur Iding (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
One of the problems that exist in schools in Kendenan Village is the lack of educators in the two hamlets that have places where educational infrastructure in the form of elementary schools is located. One of the programs implemented in Kendenan village is teaching children. The purpose of this program to teach children is 1) to assist open-education staff in schools to carry out the teaching and learning process during the COVID-19 pandemic. 2) help children to adapt to the situation, the conditions that occur. 3) help students to dare to speak and argue in front of the class. The result of this program is that children are able to participate in these activities, besides that this teaching program helps students who have difficulties in learning and adapting to the school environment.